The Brief Form of the California Odor Learning Test 3 - Frank, Conner; Murphy, Claire (Frontiers in Neuroscience, 2020)
This study explored whether a Brief Form of the California Odor Learning Test 3 (COLT), an olfactory analogue of the newly released Brief Form of the California Verbal Learning Test (CVLT 3), could retain the ability of the COLT to detect odor memory dysfunctions observed in normal aging. 52 participants, 28 young (18-30 years old) and 24 old (65 years of age and older), were administered the Brief Forms of the CVLT 3 and the COLT 3. Results indicated poorer performance in immediate and delayed odor recall in older than in younger adults. Poorer odor recognition memory performance in older adults than in younger adults was detected. This study suggests that the Brief Form of the COLT can detect differential odor learning and memory between young and older adults. Thus, the current brief test holds promise as a measure that can be incorporated into studies that demand a brief, non-invasive test capable of detecting impairment in olfactory function.